ANALISIS DAMPAK LALULINTAS (ANDALALIN) PADA KAWASAN KOMERSIL JALAN AHMAD YANI PEKANBARU - Parada Afkiki Eko Saputra (Universitas Quality, 2018)
The Ahmad Yani road section is part of the main road in the city of Pekanbaru where the activity on this road is quite high. This road section is a transportation route that is used by the community if you want to go to the commercial area on the Ahmad Yani road, namely the Santa Maria Elementary School, Santa Maria Hospital, and Kodim Market and the area of tutoring centers. Thus, the traffic flow on this road is often delayed because the volume of vehicles passing through this road is quite dense, so that it can slow down and cause conflict from other vehicles coming out into the commercial area on this road.To anticipate the influence of large enough traffic on the transportation network around this road, it is necessary to conduct a traffic impact analysis (traffic impact analysis). Based on the data of vehicles entering and leaving the 4 commercial areas through Ahmad Yani Street, based on the survey results, it was found out through data volume. Based on Ahmad Yani's geomteric condition, the entrance to the commercial area is still feasible through the Ahmad Yani road section. But for the study and market library area. The need for parking arrangements and availability of parking lots. So that the vehicle does not park on the body Ahmad Ahmad's road. As well as the need for an exit arrangement for the Santa Maria school area through the Ramayana road. Likewise with the Santa Maria Hospital area, the entrance can still be done through Ahmad Yani Street, but for the exit of the vehicle, it is hoped that you can pass the road behind the hospital, which is the Papaya Road. That way the conflict of vehicles coming out of the hospital can be reduced on the Ahmad Yani road.